Global Asymptotic Stability of Stochastic Nonautonomous Lotka-Volterra Models with Infinite Delay - Fengying Wei; Yuhua Cai (Abstract and Applied Analysis)
A kind of general stochastic nonautonomous Lotka-Volterra models with infinite delay is investigated in this paper. By constructing several suitable Lyapunov functions, the existence and uniqueness of global positive solution and global asymptotic stability are obtained. Further, the solution asymptotically follows a normal distribution by means of linearizing stochastic differential equation. Moment estimations in time average are derived to improve the approximation distribution. Finally, numerical simulations are given to illustrate our conclusions.